The Effectiveness of the Kahoot! Interactive Learning Application in Teaching Malay Grammar to Bidayuh Students in the Interior - Angela Pamela, Singi; Fatimah, Hj Subet (Karya Ilham Publishing, 2025)
This study assesses the effectiveness of the Kahoot! in teaching Malay grammar among Bidayuh students in rural elementary schools. This quasi-experimental study involved 100 students aged 10 to 12 years who were divided into two groups: an experimental group that used Kahoot! and a group of controls that use traditional methods. Pre- and post-tests were used to measure grammar mastery before and after the intervention. The results of the study show that a collection of experiments using Kahoot! experienced a significant increase in points, namely 20.5 points (from 58.4 to 78.9), while the control group only increased by 8.6 points (from 57.6 to 66.2). In addition, the results of the questionnaire showed that the motivation level of students in the experimental group was very high, with an average score of 4.65 rather than 5, indicating that they had more fun and understanding of using Kahoot! compared to traditional methods. These findings are in line with Mayer's (2001) Multimedia Learning Theory which emphasizes the use of visual and verbal elements to improve cognitive processing. It is hoped that this study can provide guidance to teachers in introducing more interactive and effective grammar teaching methods in rural schools.